Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Effect of subsurface barrier on hydrological and stratigraphic alterations during engineering groundwater control - Xiu-Li Xue; Hao-Ying Lin; Chao-Feng Zeng; Gang Zheng; Zu-Hao Zhang; Lei Han; You-Wu Zhao (Journal of Hydrology, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Sphingobacterium bovistauri sp. nov., Isolated from the Faeces of Bos Taurus - Qiong Wang; Zhi-Qin Fang; Chen-Lu Zhang; Jian-Qiang Shen; Jian-Dong Lai; Xiu-Lin Han; Tao Lu (Current Microbiology, 2022)

Advenella mandrilli sp. nov., a bacterium isolated from the faeces of Mandrillus sphinx - Qiong Wang; Xiu-Lin Han; Zhi-Qin Fang; Chen-Lu Zhang; Chun Li; Tao Lu (Antonie van Leeuwenhoek, 2022)

Sphingobacterium rhinopitheci sp. Nov., isolated from the faeces of Rhinopithecus bieti in China - Xiu-Lin Han; Qiong Wang; Chen-Lu Zhang; Zhi-Qin Fang; Jian-Qiang Shen; Song Huang; Tao Lu (Archives of Microbiology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

SCI citation analysis and impact factor prediction of JZUS-B in 2008 - Han-feng Lin; Xiu-fang Wu; Yue-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)